Determinants of adherence to wrap-around care in child and family services - Noortje M. Pannebakker; Margot A. H. Fleuren; Eline Vlasblom; Mattijs E. Numans; Sijmen A. Reijneveld; Paul L. Kocken (BMC, 2019)
Abstract Background The aim of this study is to understand the determinants of adherence to wrap-around care (WAC) by professional care providers working in child and family services. WAC is a care coordination method targeting families with complex needs. The core components of WAC involve activating family members and the social network, integrating the care provider network, and assessing, planning and evaluating the care process. WAC was introduced in the Netherlands using two approaches: the network approach (NA) and the team approach (TA). Methods A cross-sectional study was conducted using a digital questionnaire targeted at care providers. After imputation of missing data, univariate and multilevel regression analyses were conducted to study the associations between adherence to the core components of WAC, the determinants of adherence and background characteristics. Results In total 145 out of 275 care providers (52.7%) responded to the questionnaire. Multilevel regression analysis showed that self-efficacy of the care providers and the way WAC is organised (NA versus TA region) were significantly associated with adherence to core components of WAC. Self-efficacy was significantly associated with all WAC core components (activating family members and the social network: β (95% confidence interval, CI) = .27(.04-.50), integrating the network of care providers: β (95% CI) = .27(.05-.50) and assessing, planning and evaluating the care process: β (95% CI) = .30(.08-.52)). The way WAC is organised was significantly associated to two core components (activating family members and the social network: β (95% CI) = .18(0.1-.37) and integrating the network of care providers: β (95% CI) = .25(.09-.42)). Conclusion The way WAC is organised and the self-efficacy of care providers who use WAC are factors that are relevant for the redesign of the strategy for introducing WAC. Longitudinal research into the predictive value of determinants of adherence to WAC is advised.